Pengaruh Kompetensi Aparatur Desa dan Sistem Pengendalian Internal terhadap Niat untuk Melakukan Fraud dalam Pengelolaan Dana Desa - Sabirin, Sabirin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The aim of this research is to determine and analyze the influence of village apparatus competence and internal control systems on intentions to commit fraud. This research is causal (causal research). The data source in this research is primary data using a questionnaire. Secondary data is in the form of documentation from various documents related to the problem being studied. The research population was all village financial leaders in Sambas Regency, namely 193 people. As for the total population, samples were taken using the simple random sampling method with sample measurements using the Slovin formula. The selected sample was 130 respondents and the data suitable for processing was 112 respondents. Before processing, data validity tests have been carried out using validity tests, reliability tests and classical assumption tests. The analysis technique used is multiple linear regression analysis. The results of the research show that the competence of village officials and the internal control system has a positive and significant effect on the intention to commit fraud, which means that the better the competence of village officials and the internal control system, the lower the intention to commit fraud in managing village funds.